ANALYSIS THE 21ST CENTURY SKILLS OF STUDENTS IN CHEMICAL EQUILIBRIUM LEARNING WITH FLIPPED CLASSROOM-COLLABORATIVE PROBLEM SOLVING MODEL - Karyadi, Prita Atria; Paristiowati, Maria; Afrizal, Afrizal (JTK (Jurnal Tadris Kimiya), 2020)
This study aimed to analyze the 21st century skills of students in learning chemical equilibrium with the Flipped Classroom-Collaborative Problem Solving model. Flipped Classroom is a learning model that students learn first outside the classroom through video, then carry out active activities in class such as discussions, presentations, making posters, and doing practicum. Collaborative problem solving is done when students discuss in solving problems for each learning activity. The research method used descriptive qualitative method. Data collection techniques were: observation, interviews, questionnaires, and reflective journals. Data analysis consisted of several stages, namely data collection, data reduction, data presentation, and verification or conclusions. Based on data analysis, this learning model made students active in learning and also made the students learn independently outside the classroom using mobile learning and searching some sources of references. In addition, students were actively involved in problem solving discussions, presentations, making projects, and practicums that were designed by students themselves. Thus it can be concluded that the Flipped Classroom-Collaborative Problem Solving learning model can train and grow students critical thinking skills, creativity and innovation skills, communication skills, and collaborative skills in learning chemical equilibrium.